Different Clinical Utility of Oropharyngeal Bacterial Screening prior to Percutaneous Endoscopic Gastrostomy in Oncological and Neurological Patients. (27th August 2014) - Kroupa, Radek; Jurankova, Jana; Dastych, Milan; Senkyrik, Michal; Pavlik, Tomas; Prokesova, Jitka; Jecmenova, Marketa; Dolina, Jiri; Hep, Ales
Abstract : Background . The aim of this study was to monitor oropharyngeal bacterial colonization in patients indicated for percutaneous endoscopic gastronomy (PEG). Methods . Oropharyngeal swabs were obtained from patients prior to PEG placement. A development of peristomal infection was evaluated. The analysis of oropharyngeal and peristomal site pathogens was done. Results . Consecutive 274 patients referred for PEG due to neurological disorder or cancer completed the study. Oropharyngeal colonization with pathogens was observed in 69% (190/274), dominantly in the neurologic subgroup of patients ( P < 0.001). Peristomal infection occurred in 30 (10.9%) of patients and in 57% of them the correlation between oropharyngeal and peristomal agents was present. The presence of oropharyngeal pathogens was assessed as an important risk factor for the development of peristomal infection only in oncological patients (OR = 8.33, 95% CI: 1.66–41.76). Despite a high prevalence of pathogens in neurological patients, it did not influence the risk of peristomal infection with the exception for methicillin resistant Staphylococcus aureus (MRSA) carriers (OR 4.5, 95% CI: 1.08–18.76). Conclusion . During oropharyngeal microbial screening prior to the PEG insertion, the detection of pathogens may be a marker of the increased risk of peristomal infection in cancer patients only. In neurological patients the benefit of the screening is limited to the detection of MRSA carriers.